College premium: uma análise para o Brasil urbano e rural para filhos residentes com os pais nos anos de 2000 e 2010 - Moura Sá, Jairon Suel de (2018)
This work aims to measure the return of higher education, called in the literature ascollege premium, to Brazil Urban and Rural, based on information from the 2000 and 2010 censuses. It was sought to differentiate from the other works found in the literature when considering in the analysis only the kangaroo generation, thus allowing, to information about the familiar background to measure this effect. In addition, the work sought to address the problem of sample selectivity and endogeneity, present in the income equation, through Heckman's correction and the estimation of the Local Medical Effects of Treatment (LATE) using instruments (if the father is the mother or not upper superior) after testing their validation. From the results, it was observed that for Brazil Urban, it is not valid, what is the OLS for a return of education, which is for Rural Brazil the estimation of LATE was appropriate. For Brazil and Brazil Urban, the decrease of the premium college from 2000 to 2010 was observed, which indicates that there are factors that are interfering in the wage dynamics. For Rural Brazil, it was observed that individuals with higher education with parents with higher education compared to those without higher education with parents without higher education were also impacted by the reduction of wages, however, when controlling the ability to enter level, there was a wage increase from 2000 to 2010, indicating that there is a delay in relation to the impact of higher level expansion and work dynamics for individuals living in the rural area.